Álgebras de Nakayama hereditárias por partes - Tobias Fernando Pinto (2023)
In this work we introduce some tilting complexes for acyclic Nakayama algebras and describe their endomorphism algebras. We use such complexes to show that any acyclic Nakayama algebra is derived equivalent to an incidence algebra of poset. We also generalize the result of Happel and Seidel on the classification of piecewise hereditary truncated Nakayama algebras for two classes of Nakayama algebras: simple pullback and simple pushout of truncated Nakayama algebras.